AN ELECTROPHORETIC STUDY OF SCORPION VENOM - ORNELAS VALDES, OSCAR; BOLIVAR, J IGNACIO (HARVARD UNIVERSITY, CAMBRIDGE, MA, EUA, 1948)
Telsons (tails) of 2000 scorpions were ground and processed for electrophoretic analysis Eight components were detected, the relative percentages and mobility of which are cited
CIENC MEX
Keywords: ELECTROPHORETIC STUDY, SCORPION VENOM; MULTIDISCIPLINARIA; ETOLOGIA; INSECTOS